Synthesis, crystal structure and Hirshfeld surface analysis of a coordination compound of cadmium nitrate with 2-aminobenzoxazole - Surayyo Razzoqova; Yodgor Ruzimov; Akobir Toshov; Batirbay Torambetov; Aziz Ibragimov; Jamshid Ashurov; Shakhnoza Kadirova (Acta Crystallographica Section E: Crystallographic Communications)
A coordination complex of cadmium nitrate [Cd(NO3)2] with 2-aminobenzaxole (2AB; C7H6N2O), namely, tetrakis(2-aminobenzoxazole-κN1)bis(nitrato-κO)cadmium(II), [Cd(NO3)2(2AB)4], has been synthesized from ethanol solutions of Cd(NO3)2·H2O and 2AB. The asymmetric unit comprises half a molecule of [Cd(NO3)2(2AB)4], with the CdII atom positioned on a twofold rotation axis. In the completed molecular complex, four 2AB ligands and two nitrate anions each coordinate monodentately to the CdII atom, leading to a distorted octahedral coordination environment. The crystal structure of [Cd(NO3)2(2AB)4] exhibits several N—H...O interactions, resulting in the formation of a layered assembly parallel to (001). Hishfeld surface analysis was used to quantify the intermolecular interactions.